Assessment of the economic value of heritage tourism in three Western Australian locations - Hughes, Michael; Carlsen, Jack; Wood, David (Heritage Council WA, 2005)
This study estimated the direct yearly tourist expenditure at three locations in Western Australia considered to have significant cultural heritage values - the cities of Fremantle and Albany and the Town of New Norcia.Visitor expenditure surveys were used to estimate the average expenditure per visitor per day in Fremantle and Albany. The annual expenditure of all tourists was then calculated by multiplying this figure by the average number of annual overnight visitors (domestic and international) and then multiplying by the average length of stay in the respective cities. Data for New Norcia were taken primarily from secondary sources as a visitor survey was not possible. Subsequently, no individual daily spend figure could be calculated; only total annual expenditure could be estimated.In order to determine the proportion of the total overnight visitor expenditure which could be directly attributable to cultural heritage, an attribution factor was generated using a number of variables derived from the visitor surveys and secondary sources. The attribution factor was multiplied by the total annual visitor expenditure to create a best estimate of the economic value of heritage tourism.